Diluted bitumen weathered under warm or cold temperatures is equally toxic to freshwater fish - Gutierrez-Villagomez, Juan Manuel; Lara-Jacobo, Linda Ramona; Gauthier, Charles; Patey, Geraldine; Xin, Qin; Triffault-Bouchet, Gaëlle; Dettman, Heather D.; Langlois, Valerie S. (Frontiers in Environmental Science, 2024)
Canada is one of the main petroleum producers in the world. Through its oil sands exploitation, a viscous bitumen mixed with sand, water, and clay is being produced. This bitumen is so viscous that approximatively 20-30% of diluent needs to be added to ease transportation, resulting in a mixture called diluted bitumen (dilbit). The transport of dilbit through North America comes with a potential risk for oil spills in freshwater ecosystems at any time of the year. In this study, a mesoscale spill tank was used to study dilbit spills in freshwater to understand the effect of cold (winter-like) vs warmer (spring-and fall-like) water temperatures on its natural weathering and their toxicity to fathead minnow (Pimephales promelas) embryos. Water samples were collected weekly during two consecutive 35-day experiments ran at either 2 or 15 °C. Each week, fish larvae were exposed for seven days, and water analysis was performed. Chemical analysis showed that the volatile organic compound, total organic carbon, and polycyclic aromatic hydrocarbons concentration decreased in both experiments with time, while fish larvae exposed to both temperature settings yielded increased abnormalities, EROD activity, CYP1A, and glutathione Stransferase mRNA expression levels, and decreased heart rate. Importantly, there were no major differences between the temperature regimes on dilbit weathering, highlighting that if a spill occurs